(untitled) (LACCEI, 2024)
Bacteria are an important biological component present in bioaerosols and can cause disease in humans and animals and damage vegetation. In the city of Cartagena de Indias there is limited information on the environmental bacteria present in the air and the microbiological quality in that environment. Therefore, the purpose of this study was to evaluate the concentration of airborne bacteria present in an HEI in the city of Cartagena de Indias and to determine the influence of weather conditions on the concentration of bacterial bioaerosols. 128 outdoor air samples were collected with a cascade impactor over 4 months. Total bacteria count, and parameters such as temperature, relative humidity, and wind speed were monitored during the 16 sampling campaigns. The results showed that the average concentration of bacteria was 24.84 ± 8.02 CFU/m3. Furthermore, they indicated that these bacterial bioaerosols are mainly constituted by gram-positive bacteria (92%), the dominant genera being Staphylococcus and Bacillus. The concentration of bacteria in the air of the IES was mainly influenced by the wind speed.